Analysis Of The Impact Of Jakarta-Rotterdam Sister City Cooperation In Flood Water Management - Wijaya, Nadia Puspita; Saimona, Putri Fasa; Kharisma, Rizka; Anjeli, Dyah Sekar Ayu (Faculty of Social and Political Sciences - Universitas Wahid Hasyim, 2024)
Flood is a problem that often occurs in Jakarta and has encouraged Jakarta to collaborate with Rotterdam in the Netherlands thru Sister City which also has the same problem, but now Rotterdam has become a flood-free city. This cooperation is carried out on the basis of the similarities shared by Jakarta and Rotterdam. In conducting this research the authors used qualitative research methods. By collecting various information related to the Jakarta-Rotterdam cooperation from previous research and all sources from the internet, this research seeks to analyze its impact by looking at several aspects including environmental, developmental, transportation, political, and economic aspects. In this study the authors use the concepts of paradiplomacy, sister city, and water management. From this research, it was found that although this sister city collaboration has not been able to reduce floods one hundred percent, still, this collaboration has brought several good impacts. Keywords: Flood, Jakarta, Rotterdam, Sister City